SIMULATED ANNEALING MODEL FOR RETICULATE EVOLUTION IN MOLECULAR SEQUENCES - ASHOK KUMAR DWIVEDI,; DR. USHA CHOUHAN, (International Journal of Pharma and Bio Sciences, 2013)
The molecular sequence in the nature are evolved rather than invented. They are adopted from preexisting sequences. The conventional assumption on of independent evolution has been challenged by the biological evidence of hybridization, horizontal gene transfer and recombination. In such a scenario classical approaches of representing evolution by phylogenetic tree construction method fails to represent evolution. To represent such an evolution we need network models called reticulate networks. Inference of such a network given some optimization criterion like maximum likelihood or maximum parsimony have been proved to be NP-complete, so we need a model which can provide a feasible low cost solution. In this paper we propose a model based on simulated annealing which provides a global optimum solution. This method is evaluated with other available method which gives promising results.